Literature Review: Unemployment Crisis, Maintaining the Dignity and Welfare of the People - Muhammad Fauzi; Xie Guilin; Deng Jiao (Sharia Oikonomia Law Journal, 2023)
Unemployment is a macroeconomic problem that affects humans directly and is the most serious problem. Unemployment can have a negative impact, both on yourself, your family, and the surrounding environment. Islam has warned its people not to let anyone become unemployed so they don't fall into poverty, for fear that poverty can lead people to do anything, including harm. This study aims to analyze the unemployment crisis and its relationship with the dignity and welfare of the people. This research is a library research in which the data sources are obtained from document materials and library materials as well as other supporting documents. This study obtained the result that maintaining dignity in Islam is an important value. There are many factors that can cause a person to experience unemployment, such as economic conditions, changes in the job market, and a lack of adequate job opportunities. In order to maintain the dignity and welfare of the people by not becoming unemployed, there are several ways or efforts.